ANALISIS RASIO KEUANGAN UNTUK MENGUKUR TINGKAT KINERJA KEUANGAN PADA PT. BPR TUAH NEGERI MANDIRI PEKANBARU - Meiza Hestuti; Caska '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Development of Rural Bank, which grew rapidly in Indonesia trigger competition among BPR. It was a challenge for management to manage all activities of BPR in order to realize a good condition and healthy BPR. The purpose of this study was to determine how well the level of financial performance BPR Tuah Negeri Mandiri Pekanbaru based on financial ratios of liquidity, solvency, and profitability during the period of 2010 s / d in 2014.The results showed that the level of liquidity PT BPR Tuah Negeri Mandiri Pekanbaru over the last 5 years have a poor performance. While the solvency ratio PT BPR Tuah Negeri Mandiri Pekanbaru from 2010 through 2014 are in less than good condition or insolvable. And the rentabillitas ratio of PT BPR Tuah Mandiri Pekanbaru State as a whole is in good condition.Based on the results of this study concluded that the financial performance at PT BPR Tuah Negeri Mandiri has a poor performance. For that management should further improve the professionalism of its performance.Keywords: Ratio, Performance